Causes of hospital readmission with heart failure at Muhimbili National hospital: Tanzanian experience (Tanzania Medical Journal, 2009)
Background: Readmission rates for patients discharged with heartfailure approaches fifty percent within six months. Identifying factors causing re-admissions in these patients would help cliniciansto strategise ways to reduce the need for hospitalization.Broad Objectives: To study the demographic characteristics,underlying , precipitating and facilitating causes among patients readmitted with heart failure. Also to identify problems faced by thepatients in the follow up programme.Study Design: Descriptive prospective case study.Study Setting: Muhimbili National Hospital, Dar-es-Salaam,Tanzania.Measure of Outcome: Identify causes leading to re-admission amongpatients with heart failure.Subject: Ninety seven consecutive patients re-admitted in the medicalwards with heart failure.Interventions: A detailed medical history, clinical examination, bloodtests, ECG and echocardiographic evaluation were performed.Results: A total of 97 patients [56 females and 41 males] werestudied. Their mean age was 39.5 years with a range of 8 to 76 years.The major underlying clinical causes for readmission were:cardiomyopathies, hypertensive heart disease, rheumatic heartdisease and pericardial disease. The common precipitating causes forreadmission were: infections, anaemia hypertension andarrhythmias. The important facilitating causes were: inadequatemedical treatment, poor compliance inadequate follow up and poorknowledge of the patients.Conclusion: Extra efforts should be made by the clinicians andhealth care providers in improving their prescription habits as wellas educating the patients about their disease, compliance and riskfactor for cardiovascular disease so as to reduce readmissions.Keywords:  Heart failure, Muhimbili Tanzania